Priority based data gathering using multiple mobile sinks in cluster based UWSNs for oil pipeline leakage detection - Goyal, Nitin; Kumar, Ashok; Popli, Renu; Awasthi, Lalit Kumar; Sharma, Nonita; Sharma, Gaurav (Cluster computing, 2022)
Energy efficient and completely reliable data gathering in resource constrained sparse Underwater Wireless Sensor Networks (UWSNs) is challenging and requires dedicated routing techniques. Routing having mobility assistance employs a Mobile Sink (MS) or a mobile relay for data gathering. It mitigates transmission power consumption as well as relaying overhead. But multiple MSs should be deployed in order to reduce the load of a single MS. The visiting schedule of each MS should consider the priority of data, data gathering delay and buffer overflow of each sensor. In order to address these issues, a priority-based data gathering scheme using multiple MSs for clustered UWSN is proposed to help in pipeline leakage detection under the water. In this work, each MS is deployed in such a way so that it can move in both the directions i.e., top to bottom or bottom to top. When a Cluster Head (CH) receives critical data, it sends an emergency notification to the nearest MS via other CHs. Upon receiving the emergency notification, MS immediately visits that CH to gather the critical data (oil leakage).